IDENTIFICATION OF ?-HEMOLYSIS STREPTOCOCCUS SPECIES ISOLATED FROM NASAL AND TONSILLAR’SWINE USING BACITRACIN TEST - Suardana, I Wayan; Dinarini, Ni Made Ayu Aryati; Sukrama, I Dewa Made (Buletin Veteriner Udayana, 2021)
Streptococcosis is a disease caused by Streptococcus sp. , with clinical manifestations such as polyarthritis, septicemia, and meningitis. ?-hemolytic Streptococcus strains are known as one of the important pathogenic bacteria that cause serious illness. The bacteria enter their host through wounds, abrasions, food, or the immune system's decrease. This study aimed to determine the presence of ?-hemolytic Streptococcus spp in pigs raised on the people's farms in Punggul and Bongkasa Villages Abiansemal, Badung, Bali.  As many as 47 isolates isolated from nasal mucosa swabs and tonsils of pigs were cultured on blood agar media, continued by planted them on Brain Heart Infussion (BHI) agar. Gram staining, catalase, and oxidaase tests were performed as biochemical tests to complete the identification of isolates. Finally, the bacitracin test was conducted on several isolates characterized with ?- hemolytic Streptococcus to differentiate Streptococcus pyogenes strains from others. The results show, 8 out of 47 (17%) samples tested are presumptive ?-hemolytic Streptococcus. Furthermore, the bacitracin test clarifies 3 out of 8 (37.5%) ?-hemolytic isolates are S. pyogenes , and the remaining 5 out of 8 (62.5%) are non-pyogenes ?-hemolytic Streptococcus .